1978
DOI: 10.1111/j.1365-2605.1978.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Binding Proteins and Androgen Levels in the Human Testis and Epididymis

Abstract: The human testis and epididymis contain two distinct androgen binding components, one with physicochemical properties identical to the androgen receptor found in other target tissues and another, androgen binding protein (ABP), which shares the same binding characteristics as human testosterone binding globulin (TeBG). Simultaneous assays of ABP and corticosteroid binding globulin (CBG, an exclusive blood protein) in the same testicular extracts suggest that androgen binding to the second component could be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

1980
1980
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…This might be due to differences in the age of the patients or in methodology. Testosterone concentrations in epididymides were in close agreement with those re- ported before [23], but again DHT epididymal levels were somewhat higher. Nevertheless, the already mentioned study and ours agree in the finding of much higher relative and absolute concentration of testosterone in testis than in epididymis [13, 231.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This might be due to differences in the age of the patients or in methodology. Testosterone concentrations in epididymides were in close agreement with those re- ported before [23], but again DHT epididymal levels were somewhat higher. Nevertheless, the already mentioned study and ours agree in the finding of much higher relative and absolute concentration of testosterone in testis than in epididymis [13, 231.…”
Section: Discussionsupporting
confidence: 74%
“…Present data confirm the earlier observation that demonstrates the absence of a concentration gradient of DHT lengthwise in the epididymis [23]. This contrasts with findings in the rat, where the DHT concentrations decreased in the distal epididymal segments 121.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The testicular and epididymal tissue levels of steroids in the present study are consistent with those previously reported (e.g. Ruokonen et al 1972;Vihko et al 1975;McCowen et al 1979;Leinonen et al 1980;de la Torre et al 1982;Takahshi et al 1983;Purvis et al 1978;Suescun et al 1981). The present study, which has extended previous reports by measuring steroid levels in the vas deferens, as well as in the epididymis indicate that the circulating steroids are transported to these tissues accumulate and/or bind there; however, the synthesis of steroids by these organs cannot be ruled out completely.…”
Section: Discussionsupporting
confidence: 93%
“…There are few reports in the literature on measurements of testicular contents of testosterone Morse et al 1973;Ruokonen et al 1972;Purvis et al 1978;Nieschlag et al 1979;Harnmond et al 1978) and therefore, the significance and diagnostic value of this determination has not been fully established. Our mean value of 520 ?…”
Section: Discussionmentioning
confidence: 99%